Numerical performance of healthy processing for HMF content in honey - Alias, Norma; Ching, Koo Suey; Karim, Alyani Nazeeha Ab; Al-Rahmi, Waleed Mugahed; Al-Maatouk, Qusay (International Journal of Engineering and Technology, 2018)
The objective of this study is to develop a kinetic model correlating the effect of heating temperature and the duration of thermal treatment on HMF formation for different types of honey from different geographical locations. In this study, the experimental data from previous re-search papers for European and Asian honey was collected from year 1999 to 2012. The data was analysed and performed visually in graphical representation to draw the relationship between the factors. Then, a descriptive mathematical model was developed by using Math Work to correlate the parameters and the model was validated based on the data from Malaysian and European honey samples. The study showed that both heating temperature and duration could accelerate the production of HMF content in honey. The formation of HMF con-tent is proportionally increased with the increase of heating temperature and duration.